Flight ways : life and loss at the edge of extinction - Van Dooren, Thom, 1980- (New York : Columbia University Press, 2014)
"A leading figure in the emerging field of extinction studies, Thom van Dooren puts philosophy into conversation with the natural sciences and his own ethnographic encounters to vivify the cultural and ethical significance of modern-day extinctions. Unlike other meditations on the subject, Flight Ways incorporates the particularities of real animals and their worlds, drawing philosophers, natural scientists, and general readers into the experience of living among and losing biodiversity. Each chapter of Flight Ways focuses on a different species or group of birds: North Pacific albatrosses, Indian vultures, an endangered colony of penguins in Australia, Hawaiian crows, and the iconic whooping cranes of North America. Written in eloquent and moving prose, the book takes stock of what is lost when a life form disappears from the world -- the wide-ranging ramifications that ripple out to implicate a number of human and more-than-human others. Van Dooren intimately explores what life is like for those who must live on the edge of extinction, balanced between life and oblivion, taking care of their young and grieving their dead. He bolsters his studies with real-life accounts from scientists and local communities at the forefront of these developments. No longer abstract entities with Latin names, these species become fully realized characters enmeshed in complex and precarious ways of life, sparking our sense of curiosity, concern, and accountability toward others in a rapidly changing world"--
Introduction : telling lively stories at the edge of extinction -- Fledging albatrosses : flight ways and wasted generations -- Circling vultures : life and death at the dull edge of extinction -- Urban penguins : stories for lost places -- Breeding cranes : the violent-care of captive life -- Mourning crows : grief in a shared world -- Epilogue : a call for stories.
Includes bibliographical references (pages 165-183) and index.
Keywords: Birds -- Extinction